The potential of calcium carbonate as additive and microwaved sewage sludge ash as cement replacement in mortar brick - Muhammad Aizat, Azed (2016)
The production of sewage sludge from waste water treatment plant is also increasing every year. Its high content of heavy metal were harmful and must be dump in proper way in land fill to prevent pollution that will affect the soil condition surroundings. Furthermore, eggshell in Malaysia has founded as one of the valuable wastage that not being utilized usefully. Research found that Calcium Carbonate (CaCO3) found in eggshells giving hardness and strength to things. Approximately 94% of a dry eggshell is calcium carbonate. Nowadays, as the construction industries develop rapidly, the demand of cement sand brick has also increased. This will lead to increased cement production and emission of carbon dioxide because the cement industry one of the major contributor of carbon dioxide emission in the world. Hence, this research is helping in reducing the pollution and usage of cement with replacing cement partially with the sewage sludge ash (SSA), and also helping reducing the waste to environment by using eggshell powder as additive to increase the strength of the brick mortar. The sewage sludge is incinerated in the microwave with medium high temperature for 30 minutes and grind into powder form while the dry eggshell is only grind into the powder form after 24hour of drying process under the sun. Four different percentages of eggshell powder and 10% fixed of SSA are used to test the brick mortar in term of compressive strength, flexural strength and also water absorption. The XRD test was also carried out to investigate the composition of eggshell powder and also microwaved SSA (MSSA). Results shows that the eggshell powder with 5% and 10% MSSA is the most optimum percentage with highest flexural and compressive strength, with lowest water absorption compared to control samples